Report and diagnoses of Hambletonia pseudococcina Compere (Hymenoptera: Encyrtidae) and Pseudiastata sp. (Diptera: Drosophilidae): Natural enemies of Dysmicoccus brevipes (Cockerell) (Hemiptera: Pseudococcidae) in Valle del Cauca, Colombia - Kondo, Takumasa; Woolley, James B.; Campos-Patiño, Yenifer (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
During a study carried out to determine the prevalence of mealybugs in pineapple (Ananas comosus) orchards conducted in the department of Valle del Cauca, Colombia, the parasitoid wasp Hambletonia pseudococcina Compere, 1936 (Hymenoptera: Encyrtidae) and the predatory fly Pseudiastata sp. (Diptera: Drosophilidae) were found in association with the pineapple mealybug Dysmicoccus brevipes (Cockerell, 1893) (Hemiptera: Pseudococcidae). These two natural enemies are briefly diagnosed and illustrated. This is the first record of the genus Pseudiastata in Colombia.